Health literacy in action: Kaupapa Māori evaluation of a cardiovascular disease medications health literacy intervention. (June 2019) - Carlson, Teah; Moewaka Barnes, Helen; McCreanor, Tim
The healthcare system is complex and challenging to virtually everyone but more so to those who are marginalised, impoverished, and isolated—all factors that exacerbate health literacy barriers. This article reports on an analysis of qualitative data collected for a kaupapa Māori evaluation of a Cardiovascular Disease Medications Health Literacy Intervention . The evaluation study involved a kaupapa Māori evaluation of the effectiveness of the intervention and the discussion of wider learnings in relation to health literacy interventions with Māori and other Indigenous communities. Findings are grouped into three key themes: Whakaaro, tūrangatira, and whanaungatanga. Whakaaro—fluidity of understanding—refers to the importance of maintaining patient medication knowledge and nurturing relationships between patients and health professionals. Tūrangatira—presence—refers to changes in participation practices between patients and health professionals, as well as the limitations and outcomes of the intervention approach. Whanaungatanga—building relationships—covers the intervention structure and design and the role of the research nurse. This study highlighted that the responsibility for improving health literacy lies with everybody in making substantial systemic change. In this intervention, the focus of responsibility for building health literacy skills in patients and whānau (family) sat with front-line health professionals.